A riposte to ostracism and tolerance to workplace incivility: a generational perspective. Issue 2 (5th March 2018) - Abubakar, A. Mohammed; Yazdian, Taraneh Foroutan; Behravesh, Elaheh
Abstract : Purpose: Workplace mistreatment and aggression have become pressing issues in today's multi-generational workplace. Yet, to date, the issue of investigating the impacts of passive and active types of mistreatment simultaneously on different generations has been widely neglected in the management literature. The purpose of this paper is to empirically explore the resultant effects of active (i.e. workplace tolerance to incivility) and passive (i.e. workplace ostracism) mistreatments on negative emotion and intention to sabotage, a generational perspective. Design/methodology/approach: Data were garnered from bank employees in Nigeria ( n =320) and analyzed with the aid of a structural equation modeling technique. Findings: The data reveal that active and passive workplace mistreatments are relevant factors inflicting negative emotions and intention to sabotage, and negative emotions inflict the intention to sabotage. Furthermore, the impact of passive workplace mistreatment on negative emotion is higher among Generations X and Y cohorts, and its impact on the intention to sabotage is higher among Baby Boomers cohorts. The impact of active workplace mistreatment on negative emotion is higher among Generation Y and Baby Boomers cohorts, and its impact on the intention to sabotage is higher among Generations X and Y cohorts. Originality/value: This paper advances our knowledge concerning the reactional response of employees to workplace mistreatment generation wise. Based on the study findings, theoretical and practical implications are identified and discussed.